The mediating roles of e-satisfaction and e-trust relationships between website features of travel agencies and online purchase intention among Malaysian generation Z - Anas, Muhammad Saufi (2025)
This study addresses a significant theoretical and empirical void by examining the precise mechanisms through which travel agencies' website features influence the online purchase intention of Malaysian Generation Z, specifically investigating the serial mediating roles of e-satisfaction and e-trust. Employing a rigorous post-positivist, deductive quantitative approach, data were meticulously collected from 600 Malaysian Generation Z respondents (aged 18-24) in SS15 Subang Jaya and Cyberjaya, Selangor, utilizing a validated 4-point Likert scale questionnaire. Comprehensive data analysis, performed using SPSS Version 25 and SmartPLS 4, encompassed frequency, descriptive, reliability, factor analysis, regression, and serial mediation analyses. The findings conclusively demonstrate that critical website features, including security (cashless payment, personal data protection), web design (ease of use, visual appeal, navigation), and information quality (price information, online reviews), significantly contribute to Generation Z's e-satisfaction. This e-satisfaction, in turn, is a powerful determinant of e-trust, and most crucially, both e-satisfaction and e-trust serially mediate the relationship between website features and online purchase intention, illustrating how these psychological states sequentially bridge the gap between digital engagement and actual buying decisions. A key insight reveals that while basic usability is a fundamental expectation, true e-satisfaction for this demographic arises from a more comprehensive, integrated digital experience, emphasizing the importance of perceived security and end-to-end data protection. Theoretically, this research significantly expands the Technology Acceptance Model (TAM) by empirically validating the sequential mediating roles of e-satisfaction and e-trust within the context of intangible, high-value online travel purchases for Generation Z, offering a nuanced understanding of contemporary consumer behavior. Practically, these findings compel travel agencies to strategically invest in robust security, transparent data protection, and visually stimulating, integrated web designs that transcend mere functionality, recognizing that fostering trust through engaging interactions is a multi-step process vital for converting digital interest into loyal customers in the dynamic online travel landscape. Novelty of the study lies in its unique focus on the Malaysian Generation Z demographic and its detailed analysis of the multi-step trust formation process specifically for intangible travel products, providing a culturally specific and granular understanding previously lacking in generalized studies. The study is confined to Malaysian Generation Z, limiting the generalizability of findings due to the demographic's non-homogeneous nature. The focus on a specific age group (18-24) and geographic areas (SS15 Subang Jaya and Cyberjaya) may restrict broader applicability across the entire Generation Z cohort.